Case Report: SARS-CoV-2-associated immune dysfunction manifesting as concurrent fulminant type 1 diabetes mellitus and subacute thyroiditis - Fang, Wei; Wang, Huanping; Zhong, Lian; Xu, Jie; Zhu, Hongxia (Frontiers in Medicine, 2025)
ObjectivesThe association between SARS-CoV-2 infection and endocrine emergencies (such as fulminant type 1 diabetes mellitus and subacute thyroiditis) has received increasing attention. However, concurrent manifestations of these two conditions within a short period of time after infection are exceedingly rare, and the underlying mechanisms and clinical management strategies remain unclear.Case presentationA 45-year-old Chinese man developed sudden polydipsia, polyuria, and cervical pain on day 7, within 2 weeks of SARS-CoV-2 infection. The diagnosis of fulminant type 1 diabetes mellitus complicated by subacute thyroiditis (SAT) was confirmed through laboratory investigations (arterial blood gas analysis, C-peptide release test, and thyroid ultrasound) and imaging. Treatments included fluid resuscitation, continuous intravenous insulin infusion (0.1 U/kg/h), and prednisone (30 mg/day). Acidosis was corrected within 48 h, and SAT symptoms resolved by day 8. At the 6-month follow-up, SAT had completely resolved, but pancreatic β-cell function remained absent, necessitating lifelong insulin therapy.ConclusionThis case suggests that SARS-CoV-2 may induce dual-gland damage through immune injury mediated by angiotensin-converting enzyme 2 receptor and cytokine storms. Clinicians should be vigilant for acute hyperglycemia and neck pain following SARS-CoV-2 infection. Serial monitoring of blood glucose and thyroid-related parameters is essential as early intervention may improve prognosis.